The Geography of Natural Resources, Ethnic Inequality and Development - Christian Lessmann; Arne Steinkraus (Center for Economic Studies and ifo Institute (CESifo), 2017)
We study whether the spatial distribution of natural resources across different ethnic groups within countries impede spatial inequality, national economic performance, and the incidence of armed conflict. By providing a theoretical rent-seeking model and analysing a set of geocoded data for mines, night-time light emissions, local populations and ethnic homelands, we show that the distribution of resources is a major driving factor of ethnic income inequality and, thus, induces rent-seeking behaviour. Consequently, we extend the perspective of the resource curse to explain cross-country differences in economic performance and the onset of civil conflicts. We show that the inequality in the spatial distribution of resource endowments within countries drives the curse of natural resources, not the resources per se.
Keywords: D72; D74; Q32; Q34; 330; natural resources; minerals; mines; night lights; luminosity; ethnic income inequality; spatial inequality; development; civil war; conflict